2016
DOI: 10.1038/srep38866
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Interactions between Fronto-Parietal and Default Mode Networks in Impaired Consciousness

Abstract: Existing evidence suggests that the default-mode network (DMN) and fronto-pariatal network (FPN) play an important role in altered states of consciousness. However, the brain mechanisms underlying impaired consciousness and the specific network interactions involved are not well understood. We studied the topological properties of brain functional networks using resting-state functional MRI data acquired from 18 patients (11 vegetative state/unresponsive wakefulness syndrome, VS/UWS, and 7 minimally conscious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
6
22
0
Order By: Relevance
“…In addition, we also found that over the first 6 months post‐injury, patients demonstrate a significant restoration of the agonistic and (relatively) antagonistic balance between the so‐called default mode network, which overlaps with the putative internal awareness network, and the executive control network, which overlaps with the putative external awareness network. These findings are in keeping with much of the cross‐sectional literature in chronic disorders of consciousness (Demertzi et al, ; Long et al, ; Vanhaudenhuyse et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we also found that over the first 6 months post‐injury, patients demonstrate a significant restoration of the agonistic and (relatively) antagonistic balance between the so‐called default mode network, which overlaps with the putative internal awareness network, and the executive control network, which overlaps with the putative external awareness network. These findings are in keeping with much of the cross‐sectional literature in chronic disorders of consciousness (Demertzi et al, ; Long et al, ; Vanhaudenhuyse et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…It is important to understand developmental changes in task-and rest-state connectivity, as altered connectivity has been reported for numerous psychological disorders (see Cohen, 2018;Greicius, 2008, for reviews). For example, a maturational lag in DMN-to-FPN connectivity has been associated with attention-deficit/hyperactivity disorder (Sripada, Kessler, & Angstadt, 2014), and abnormal resting-state functional connectivity between DMN and FPN has been found in patients with obsessive compulsive disorder (Stern, Fitzgerald, Welsh, Abelson, & Taylor, 2012) and with impaired consciousness (Long et al, 2016). Future work could investigate whether precuneus's task-and rest-based connectivity is altered in atypical development and whether any such deviations from typical connectivity development correspond to behavioral or psychological impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the left precuneus, a key hub structure from the default mode network (DMN). The precuneus is engaged in self-related processing (Zhang and Chiang-shan, 2012), episodic memory (Ren et al, 2018), awareness and conscious information processing (Kjaer et al, 2001;Vogt and Laureys, 2005;Long et al, 2016). The second is a portion of the left orbitofrontal cortex, which is thought to encode predicted values of potential rewards (Gottfried et al, 2003).…”
Section: Low Integration In Doc Networkmentioning
confidence: 99%